2018
DOI: 10.3390/biology7010009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sex Steroids on Fish Leukocytes

Abstract: In vertebrates, in addition to their classically reproductive functions, steroids regulate the immune system. This action is possible mainly due to the presence of steroid receptors in the different immune cell types. Much evidence suggests that the immune system of fish is vulnerable to xenosteroids, which are ubiquitous in the aquatic environment. In vivo and in vitro assays have amply demonstrated that oestrogens interfere with both the innate and the adaptive immune system of fish by regulating the main le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 160 publications
0
24
0
1
Order By: Relevance
“…For example, Seemann et al ( 2013 ) found that estradiol did not affect the expression of tgfβ in the head kidney or change the level of TGFβ protein in the blood of juvenile sea bass. In gilthead seabream, estradiol increased the activity of MMP2 and MMP9 in testicle leukocytes (Chaves-Pozo et al 2018 ). It also accelerated wound repair after scale removal in gilthead sea bream possibly via ERβs.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Seemann et al ( 2013 ) found that estradiol did not affect the expression of tgfβ in the head kidney or change the level of TGFβ protein in the blood of juvenile sea bass. In gilthead seabream, estradiol increased the activity of MMP2 and MMP9 in testicle leukocytes (Chaves-Pozo et al 2018 ). It also accelerated wound repair after scale removal in gilthead sea bream possibly via ERβs.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, these and other studies imply that to accurately define a stressotope, the range of abnormal values in distress physiological adjustments, the scope of stressome components to be included in the analysis of allostatic load and the intersex differential responses to severe stressors, should necessarily be taken into account. Considering that in teleosts, as in the rest of vertebrates, steroids regulate reproductive outcomes but also metabolism, stress responses, behavior and immune function, usually in a seasonal way (133, 134), the differential effect of estrogens- and testosterone-derived mediators must be included in the stressome catalog.…”
Section: Janian Phenomesmentioning
confidence: 99%
“…Gonads are immune-privileged sites as they need to prevent immune responses against meiotic germ cells (Maddocks and Setchell, 1990). Immune cells present sexual steroid receptors not only in mammals (Kovats et al, 2010) but also in fish (Chaves-Pozo et al, 2018). Thus, sexual steroids regulate the immune system in addition to classical reproduction-related functions in vertebrates.…”
Section: Introductionmentioning
confidence: 99%